The evolution of parasites from their hosts: intra- and interspecific parasitism and Emery's rule. - Lowe, Roger M (2002)
In some taxa of Hymenoptera, fungi, red algae and mistletoe, parasites and their hosts are either sibling species or at least closely related (Emery's rule). Three evolutionary mechanisms have been proposed for this phenomenon: (i) intraspecific parasitism is followed by sympatric speciation; (ii) allopatric speciation is followed by secondary sympatry and the subsequent parasitism of one sibling species by the other; and (iii) allopatric speciation of a species with intraspecific parasitism is followed by secondary sympatry, in which one species becomes an obligate parasite of the other. Mechanisms (i) and (ii) are problematic, while mechanism (iii) has not, to our knowledge, been analysed quantitatively. In this paper, we develop a model for single- and two-species evolutionary stable strategies (ESSs) to examine the basis for Emery's rule and to determine whether mechanism (iii) is consistent with ESS reasoning. In secondary sympatry after allopatric speciation, the system's evolution depends on the relative abundances of the two sibling species and on the proportional damage wrought by parasites of each species on non-parasitic members of the other. Depending on these interspecific effects, either the rarer or the commoner species may become the parasite and the levels of within-species parasitism need not determine which evolves to obligate parasitism.